A produção de habitações de interesse social em Maringá - Ramos, Felipe (2015)
The present moment of the capitalist mode of production leads us to investigate the reasons that lead to the split of housing production as a necessary apparatus of the reproduction of capital. To analyze the housing problem from the formation merchandise made based on the exchanged makes the city the locus of the buildings of "concrete" - guided in the correlations of forces which relentlessly appropriating these spaces. However, the search for production of urban space consolidated in new ways for achievement and accumulation of capital through co-option and virtually all levels of reality. The extent of the commodity form for housing causes occurs an appreciation of real estate in different places and points of cities, a factor which does not present itself differently in Maringa, further adding high contributions to the capitalist construction of buildings. Such factors mean that a considerable part of the income of families - especially the working class have their income committed to the excessive burden of housing finance. The object to be studied in the research are the dwellings in Maringa (PR), a priori divide the projects to be studied in social housing and market- this last sector, it enabled us to verify the property of MRV which calls their housing projects Popular residential, the market sector still served us as parameters to analyze the production of social housing. The reasoning supported the historical movement pointed out that the production of affordable housing has always been characterized by interventionist state measures, but the current time falls within other specifics and contradictions, such as the privatization of the buildings of social housing and lack of state control, and its role allocate the funds from lending directly to private companies the local construction to carry out the projects, backed mechanisms in market- logic therefore subsequently chose to characterize both market housing sectors. Our task was to grasp the mechanisms that led to recovery of the housing production in urban areas of Maringa, especially starting from 2009 with the establishment of the MCMV Program (MCMV) and the methodology to be used in this research to obtain results developed through search and perform the analyzes of reference: theoretical, technical and empirical, and the identification of the study object.